Fabrication of the Ni-NiCl2 Composite Cathode Material for Fast-Response Thermal Batteries - Tian, Qianqiu; Wang, Jiajun; Xiang, Wendi; Zhao, Jun; Guo, Hao; Hu, Jing; Han, Xiaopeng; Hu, Wenbin (Frontiers in Chemistry, 2021)
Thermal batteries with a high power density and rapid activation time are crucial for improving the fast response ability of sophisticated weapons. In this study, an Ni-NiCl2 composite was prepared via hydrogen reduction and employed as a cathode material. Discharge tests on a battery assembled using the fabricated composite revealed that its initial internal resistance decreased and the activation time reduced. Notably, the Ni-NiCl2 cathode increased the energy output by 47% (from 6.76 to 9.94 W·h in NiCl2 and Ni-NiCl2, respectively) with a cut-off voltage of 25 V; the power density of the novel battery system reached 11.4 kW/kg. The excellent performance of the thermal battery benefited from the high electrode potential and low internal resistance of Ni-NiCl2. This study contributes to the development of high-performance electrode materials for next-generation thermal battery-related technologies.